Increased Postoperative Fasting Glucose Is Associated With Unfavorable Outcomes in Patients Treated With Mechanical Thrombectomy Treatment - Shi, Zongjie; Guo, Shunyuan; Pan, Jie; Xu, Chao; Geng, Yu; Zheng, Sujie (Frontiers in Neurology, 2021)
Background and objective Hyperglycemia on admission was associated with unfavorable outcomes in stroke patients treated with mechanical thrombectomy (MT). However, little is known about the prognostic role of postoperative fasting glucose after MT. Here, we investigated whether postoperative fasting glucose (PFG) was associated with unfavorable functional outcomes in acute ischemic stroke (AIS) patients after MT treatment. Methods Consecutive AIS patients with large vessel occlusion treated with MT in our stroke center were evaluated. Admission glucose and fasting glucose levels after MT treatment were evaluated. The primary outcome was 90-day unfavorable outcomes (modified Rankin Scale score of 3-6). The secondary outcome was the occurrence of symptomatic intracranial hemorrhage (sICH) after MT treatment. The association of PFG with 90-day outcome after MT treatment was evaluated using univariable and multivariable binary logistic regression models. Results Overall, 127 patients were included. The median postoperative fasting glucose level was 6.27 mmol/L (IQR 5.59-7.62). Fourteen patients (11.02%) had sICH, and fifty-eight patients (45.67%) had unfavorable outcomes at 90 days after MT. After adjustment for potential confounding factors, PFG level was an independent predictor of 90-day unfavorable outcome (OR 1.265; 95% CI 1.017-1.575; p=0.035) and sICH (OR 1.523; 95% CI 1.056-2.195; p=0.024) after MT. In addition, older age, higher baseline NIHSS score, and higher postoperative NLR were also associated with unfavorable outcomes at 90 days after MT treatment. Conclusions Increased PFG is associated with unfavorable outcomes at 90 days and an increased risk of sICH in acute ischemic stroke patients treated with MT treatment.